Community of Inquiry Approach: The Meaning of Presence for MOOC Learning in Zoonoses Control Training - Luqman Suyanto Putra; Cecep Kustandi; Murti Kusuma Wirasti; Maman Maman; Tri Budi Gunawan (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
Massive Open Online Course (MOOC) have become a flexible learning solution that is widely accessible. Drop Out is still a problem in MOOC learning. Many factors cause participants to choose not to continue their studies in MOOC, including limited study time and high workloads. The meaning of presence in online learning is often overlooked, even though it plays an important role in enhancing participant engagement and success. This study aims to describe the needs of MOOC participants for the meaning of presence in online learning, inspired by the community of inquiry framework. The survey was conducted with 150 graduates of Zoonoses Control Training. Data processing was conducted using Microsoft Excel to analyze the response patterns of participants. The research results show that the majority of participants responded positively to the meaning of presence in MOOC. Participants strongly agree that the cognitive presence, social presence, and teaching presence is needed in MOOC learning. These findings make an important contribution to the development of higher-quality MOOC by emphasizing the importance of creating a more inclusive and interactive learning environment. By understanding the meaning of presence in MOOC, course designers can create more engaging learning experiences and reduce dropout rates, thereby ensuring that online learning is more effective and sustainable.